2017
DOI: 10.1111/gcb.13598
|View full text |Cite
|
Sign up to set email alerts
|

Climate change‐induced vegetation shifts lead to more ecological droughts despite projected rainfall increases in many global temperate drylands

Abstract: Drylands occur worldwide and are particularly vulnerable to climate change because dryland ecosystems depend directly on soil water availability that may become increasingly limited as temperatures rise. Climate change will both directly impact soil water availability and change plant biomass, with resulting indirect feedbacks on soil moisture. Thus, the net impact of direct and indirect climate change effects on soil moisture requires better understanding. We used the ecohydrological simulation model SOILWAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(84 citation statements)
references
References 97 publications
1
78
0
Order By: Relevance
“…We report results for a future climate near the 50th percentile of the 16 GCMs based on RCP8.5, leading to ~1,370 ppm CO 2 (Van Vuuren et al, ). We present results only for RCP8.5 because results for RCP4.5 are qualitatively similar (Tietjen et al, ) and because RCP8.5 simulates a plausible scenario of heavy dependence on fossil fuels until at least 2100.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…We report results for a future climate near the 50th percentile of the 16 GCMs based on RCP8.5, leading to ~1,370 ppm CO 2 (Van Vuuren et al, ). We present results only for RCP8.5 because results for RCP4.5 are qualitatively similar (Tietjen et al, ) and because RCP8.5 simulates a plausible scenario of heavy dependence on fossil fuels until at least 2100.…”
Section: Methodsmentioning
confidence: 87%
“…There are important limitations to the use of simulation models like SOILWAT in studying the effects of plant functional groups on ecological drought. First, our analysis did not incorporate feedback (Turnbull et al, ), and vegetation changes that follow climate change further exacerbate drought in SOILWAT (Tietjen et al, ). Similarly, biomass increased by factors such as fertilization, grazing respite, or invasion by identical functional groups with greater productivity should all increase ecological drought, but grassland aboveground biomass in turn varies strongly with water availability independently of other drivers (Lauenroth & Sala, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earth greening implies that the capacity of the biospheric carbon pool is being boosted because of enhanced vegetation photosynthetic activity [7], which might be expected to mitigate the magnitude of climate warming and its associated negative effects on the earth system [1,3]. On the other hand, climate warming directly impacts the dynamics of the terrestrial vegetation biomes by increasing the frequency, duration and severity of drought and heat stress [8][9][10][11], while other studies have suggested that climate warming tends to relax temperature constraints for plant growth [12,13]. Many studies assume that plants have an optimal threshold for growth and reproduction [14], suffering cold stress when temperatures are below this threshold, and heat stress when above [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies assume that plants have an optimal threshold for growth and reproduction [14], suffering cold stress when temperatures are below this threshold, and heat stress when above [15]. Accordingly, we can deduce that when the in-situ temperature is suboptimal, climate warming may relax the temperature constraint for plant metabolism and promote its growth, while supraoptimal temperature conditions and the accompanying rise in the vapor pressure deficit and evaporation may damage the plant's cellular tissues [8,16,17]. Here, we ask: what have been the responses in diverse vegetation biomes to ongoing recent climate warming?…”
Section: Introductionmentioning
confidence: 99%